FINANCIAL PERFORMANCE ANALYSIS OF PT. PEGADAIAN CABANG BISNIS MIKRO MANADO SELATAN BEFORE AND DURING FINANCIAL RESTRUCTURING - Aulia Bacharudin; James Massie; Fitty V. Arie (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
The rapid spread of the COVID-19 outbreak has resulted in disruptions to banking performance and financial system stability. In response to this the government made one of the credit relaxation policies through credit restructuring for debtors affected by Covid 19. This debt restructuring provides relief for debtors to fulfill their obligations which indirectly the company has to opportunity to be able to allocate funds to the company’s operation first in the hope that this has an impact on imporving financial performance. This study aims to find out how the impact or influence of credit restructuring on financial performance during the covid 19 pandemic. This study uses a non-experimental quantitative approach in cross sectional, by collecting data to calculate profitability ratios, liquidity ratios, collectability ratios, which are taken from financial statements taken at PT. Pegadaian Cabang Bisnis Mikro Manado Selatan. Financial reports for 2020-2022 when the pandemic occurred. The results of this study indicate that from the data obtained from the financial statements by calculating the profitability ratio, liquidity ratio, collectability ratio, it shows that the company still has the ability to meet its obligations during this pandemic, even though the credit restructuring is extended .   Keywords: financial performance, financial restructuring, restructuring, finance